Teaching & Learning Guide for: Writing the History of the English Bible: A Review of Recent Scholarship - Bagley, Ellie G. (Religion compass, 2012)
This guide accompanies the following article: Ellie G. Bagley, Writing the History of the English Bible: A Review of Recent Scholarship, Religion Compass 5/7 (2011) pp. 300-313, 10.1111/j.1749-8171.2011.00286.x Author’s Introduction The 400th anniversary of the King James Bible (KJB) has drawn increased attention to the study of the English Bible, from its earliest versions to more recent translations and formats. In addition to the host of new publications on the subject, colleges and universities are offering a broader range of courses on the history and impact of the English Bible, both for undergraduates and graduate students. This guide is offered as an aid for instructors developing (or re-designing) courses on the English Bible, and for those interested in adding a few days or a few weeks to existing syllabi in religion, history, or literature. Engagement with primary resources is especially encouraged, and instructors may wish to supplement facsimile-reprinted and online editions with materials available at institutional libraries or in traveling exhibitions. Author Recommends 1 Norton, David. (2011). The King James Bible: A Short History from Tyndale to Today. New York: Cambridge University Press. Of the many one-volume introductions to the history of the English Bible, Norton’s stands out as both readable and containing helpful notes and bibliographies that synthesize recently published work in the field. 2 Campbell, Gordon. (2010). Bible: The Story of the King James Version, 1611-2011. New York: Oxford University Press. This is a well-written and engaging account, with especially good coverage of the reception history and American contexts of the KJB. 3 Lori Ann Ferrell. (2008). The Bible and the People. New Haven: Yale University Press. This book examines the broader cultural importance of the Bible in western culture throughout the past millennium. Sixteenth-century Bibles receive due attention, as does the subject of the Bible in America and missions and print culture in the nineteenth century. 4 Daniell, David. (2003). The Bible in English: Its History and Influence. New Haven: Yale University Press. This is generally recognized as the most thorough narrative in recent years and is well worth having students read from selectively. 5 Norton, David. (2005). A Textual History of the King James Bible. New York and Cambridge: Cambridge UP. This authoritative account of developments in the text of the KJB has helped to offset popular notions of the "classic," unchanging quality of the KJB’s text, which changed significantly in editions from the eighteenth century onwards. 6 Hamlin, Hannibal and Jones, Norman (eds.) (2010). The King James Bible after Four Hundred Years: Literary, Linguistic, and Cultural Influences. New York: Cambridge University Press. An excellent collection of essays exhibiting recent work on the literary impact and cultural significance of the KJB. 7 Helen Moore and Reid, Julian (eds.) (2011). Manifold Greatness: The Making of the King James Bible. Bodleian Library Publishing. Contributions from Diarmaid MacCulloch, Peter McCullough, Judity Maltby and others introduce readers to the traveling library exhibition first featured at Oxford’s Bodleian Library, April 22 through Sept. 4, 2011. For exhibition schedule, see: http://www.manifoldgreatness.org/index.php/see-the-exhibition/. 8 Nicolson, Adam. (2003). God’s Secretaries: The Making of the King James Bible. New York: HarperCollins. Published in Great Britain in 2003 by HarperCollins Publishers Ltd. as Power and Glory: Jacobean England and the Making of the King James Bible. A lively and informative account of the cultural context and personalities of the scholars who translated and published the KJB, 1604-1611. 9 Lemon, Rebecca, Mason, Emma, Roberts, Jonathan and Rowland, Christopher (eds.) (2009). The Blackwell Companion to the Bible in English Literature. Chichester, United Kingdom, and Malden, Massachusetts: Wiley-Blackwell. A useful guide to the scores of books and articles on the literary influence of the KJB and other English versions of the Bible. 10 Thuesen, Peter J. (1999). In Discordance with the Scriptures: American Protestant Battles over Translating the Bible. New York: Oxford University Press. A fascinating and well-researched study of the King James Only movement in twentieth-century America, centered on resistance to the Revised Standard Version of 1952 with good background on nineteenth-century contexts. Online Materials 1 http://www.kingjamesbibletrust.org/ This site provides a full list of Anniversary events, links to the "YouTube Bible" project, and a link to a digitized version of the 1611 KJB. 2 http://books.google.com/books?id=-WwKAQAAMAAJ&printsec=frontcover&dq=english+hexapla&hl=en&ei=z19ETpD3JqT00gGxm9n7Bw&sa=X&oi=book_result&ct=result&resnum=1&ved=0CDcQ6AEwAA#v=onepage&q&f=false The English Hexapla, exhibiting the six important English translations of the new testament scriptures (London: Bagster and Sons, 1841). 3 http://gallica.bnf.fr/ark:/12148/bpt6k53352s/f3.image Digital version of the Catholic Rheims New Testament, 1582, translated from the Latin Vulgate. This version and other early English translations (such as the Geneva Bible) are also available, upon institutional subscription, through the Early English Books Online resource. 4 http://books.google.com/books?id=2ipVAAAAMAAJ&printsec=frontcover&dq=pollard+records&hl=en&ei=a2BETo-fF6ra0QGwj9XeCQ&sa=X&oi=book_result&ct=result&resnum=1&ved=0CC0Q6AEwAA#v=onepage&q&f=false Pollard, Alfred W. (1911). Records of the English Bible: The Documents Relating to the Translation and Publication of the Bible in English, 1525-1611. London: Oxford University Press. 5 http://www.biblegateway.com/ This site provides searchable text for 25 early and contemporary English versions as well as in biblical languages and modern translations. 6 http://www.youtube.com/watch?v=nu9uOfDX_Tw This is the ‘video abstract’ for my article. Sample Syllabus This syllabus includes readings appropriate both to general-level courses (indicated by A) and advanced or seminar courses (B). Week 1. The King James Bible at 400: its Legacy and Influence A Bagley, Ellie G. (2011). Writing the History of the English Bible: A Review of Recent Scholarship, Religion Compass. B Prickett, Stephen. (2010). Language within Language: The King James Steamroller; and Robert Alter, The Glories and Glitches of the KJB. In: H. Hamlin and N. Jones (eds.), The King James Bible after 400 Years: Literary, Linguistic, and Cultural Influences. Week 1. Before the King James Bible A Norton, David. The King James Bible: A Short History (2011), chapter 1, "Predecessors"; Christopher de Hamel, The Book: A History of the Bible (2001), chapter 9, "Bibles of the Protestant Reformation." B Gritsch, Eric W. Luther as Bible Translator and Baker, Oswald, Luther as an interpreter of Holy Scripture in The Cambridge Companion to Martin Luther (Cambridge, 2003); Alexandra Walsham, Unclasping the Book? Post-Reformation English Catholicism and the Vernacular Bible, Journal of British Studies (2003). Week 2. Translating, Interpreting, and Reading Early English Bibles A Anne Ferrell, Lori. The Bible and the People, chapter 3, "The Politics of Translation: The Bible in English, c. 1500-1700"; David Wright, The Study and Use of the Bible: The Reformation to 1700, History of the Bible, 192-217. B Paul’s Letter to the Romans, chapters 1-8, in the Geneva Bible (1560) and the Rheims New Testament (1582) available online (see above). Week 2. The Making of the King James Bible A Norton, David. The KJB: A Short History, chapter 2, "Drafting the King James Bible," and chapter 4, "Working on the King James Bible". B Nicolson, Adam. (2003). God’s Secretaries: The Making of the King James Bible. Harper; Tadmor, Naomi. (2010). The Social Universe of the English Bible: Scripture, Society, and Culture in Early Modern England. Cambridge. Week 3. The 1611 Edition and Early Print History A Norton, David. The KJB: A Short History, chapter 5, "1611: the first edition"; Christopher de Hamel, The Book. A History of the Bible, chapter 10, "The English and American Bible Industry". B Norton, David. The Textual History of the KJB, chapter 4, "The King’s Printer at Work, 1612-1617," and chapter 5, "Correcting and Corrupting the text, 1629-1760"; selected pages from the 1611 edition and the English Hexapla, both available online. Week 3. The KJB’s Reception to 1800 A Norton, David. The KJB: A Short History, chapter 6, "Printing, editing, and the development of a standard text"; Campbell, Gordon. Bible: The Story of the King James Version (Oxford, 2010), chapter 6, "The Seventeenth Century," and chapter 7, "The Eighteenth Century". B Norton, David. (2004). A History of the English Bible as Literature, chapter 5, "The Struggle for Acceptance"; Scott Mandelbrote, Writing the History of the English Bible in the Early Eighteenth Century, In: R. N. Swanson (ed.), The Church and the Bo...